Unmasking early microglial remodeling in an Alzheimer’s disease mouse model - Saminathan, Priyanka; McArdle, Sara; Corey, Maija; Nadig, Namratha; Fang, Camille; Gibbons, Alicia; Rayadurgam, Mahati; Sharma, Sonia (Frontiers in Cellular Neuroscience, 2026)
Early neuroimmune remodeling is a critical yet understudied component of Alzheimer’s disease (AD) pathogenesis. To investigate microglial contributions to AD development prior to overt plaque deposition, we developed an open-source morphometric pipeline to systematically quantify hippocampal microglial structure and activation states in pre-plaque 5xFAD mice. Across ∼11,000 cells, we extracted multidimensional parameters including area, circularity, convex hull, branch points, nearest-neighbor distance, and nuclear features, alongside Iba1 and CD68 intensity measurements. While no significant overt gliosis was observed at this early stage, microglia from 5xFAD mice exhibited subtle trends toward increased structural complexity compared to wild-type controls. Importantly, significant sex-specific differences were detected within the CA1 subregion: male 5xFAD microglia displayed hyper-ramified morphologies consistent with enhanced surveillance states, whereas female microglia demonstrated greater density and a more reactive phenotype. Correlation analyses revealed a conserved association between microglial complexity and Iba1/CD68 expression, independent of sex or genotype, underscoring a fundamental link between cytoskeletal remodeling and phagolysosomal activity. These findings highlight the capacity of morphometric profiling to sensitively detect early, region-specific, and sex-dependent shifts in microglial phenotype before amyloid deposition. By integrating quantitative morphology with canonical molecular markers, this framework provides a robust and unbiased approach for characterizing microglial activation trajectories. Such early readouts may inform biomarker discovery and therapeutic strategies aimed at modulating microglial responses to delay or prevent AD progression.